Long-term neurodevelopmental outcome of children born to prospectively followed pregnancies of women with systemic lupus erythematosus and/or antiphospholipid syndrome. (April 2017) - Nalli, C; Iodice, A; Andreoli, L; Galli, J; Lojacono, A; Motta, M; Fazzi, E; Tincani, A
Background: Systemic lupus erythematosus (SLE) and antiphospholipid antibody syndrome (APS) are autoimmune diseases that affect women of childbearing age. Maternal IgG antiphospholipid antibodies (aPL) can cross the placenta during pregnancy and theoretically reach the fetal brain. Some studies showed an increased number of learning disabilities in these children. Objectives: To evaluate the long-term neurodevelopmental outcome of 40 children (median age 7.4 years) born to mothers with SLE and/or APS carrying positive IgG aPL during the third trimester of pregnancy. Methods: Children were checked for neurological physical exam and intellectual/cognitive functioning by the Wechsler scale for corrected age. We submitted to the mothers the Child Behavior CheckList (CBCL) and a homemade set of questions created by pediatric neurologists. Results: In all children neurological physical exam and intelligence levels were found to be normal. A cognitive impairment or a discrepant cognitive profile was found in 3 (7%) and 11 (28%) children, respectively. Learning disabilities were diagnosed in 3 children (19% of school-age children), all born to mothers with triple aPL positivity. A history of epilepsy was shown in four children (10%).Conclusions: Children born to women with SLE and/or APS may need a long-term follow-up focusing on milestones of neurodevelopment in order to detect and correct any alteration as early as possible.